Processing of Factor XII during Inflammatory Reactions - Jukema, Bernard Nico; de Maat, Steven; Maas, Coen (Frontiers in Medicine, 2016)
The contact system was originally identified as an obsolete part of the coagulation system, but it has been repeatedly implicated in inflammatory states, such as infection, as well as in allergic- and chronic inflammatory disease. Under these conditions, there is surprisingly little evidence that factor XII acts as a coagulation factor and its activity appears to be mainly directed towards activation of the kallikrein-kinin system. The contact system factors interact with pathogens, as well as cells of the (innate) immune system on several levels. Amongst others, these cells may provide negatively charged surfaces that contribute to contact activation, as well as release enzymes that feed into this system. Furthermore, cellular receptors have been identified that bind contact factors at sites of inflammation. Based on the accumulated evidence, we propose a model for enzymatic crosstalk between inflammatory cells and the plasma contact system. During these reactions, factor XII is enzymatically cleaved by non-contact system enzymes. This generates unactivated factor XII fragments that can subsequently be rapidly activated in the fluid phase. The resulting enzyme lacks procoagulant properties, but retains its proinflammatory characteristic as a prekallikrein activator.